Three-Dimensional Anthropometric Database of Attractive Caucasian Women: Standards and Comparisons. Issue 7 (October 2016) - Galantucci, Luigi Maria; Deli, Roberto; Laino, Alberto; Di Gioia, Eliana; D'Alessio, Raoul; Lavecchia, Fulvio; Percoco, Gianluca; Savastano, Carmela
Abstract : Abstract: The aim of this paper is to develop a database to determine a new biomorphometric standard of attractiveness. Sampling was carried out using noninvasive three-dimensional relief methods to measure the soft tissues of the face. These anthropometric measurements were analyzed to verify the existence of any canons with respect to shape, size, and measurement proportions which proved to be significant with regard to the aesthetics of the face. Finally, the anthropometric parameters obtained were compared with findings described in the international literature. The study sample was made up competitors in the Miss Italy 2010 and 2009 beauty contest. The three-dimensional (3D) scanning of soft tissue surfaces allowed 3D digital models of the faces and the spatial 3D coordinates of 25 anthropometric landmarks to be obtained and used to calculate linear and angular measurements. A paired Student t test for the analysis of the means allowed 3 key questions in the study of biomorphometric parameters of the face to be addressed through comparison with the data available in the literature. The question of statistical evidence for the samples analyzed being members of the populations samples reported in literature was also addressed. The critical analysis of the data helped to identify the anthropometric measurements of the upper, middle, and lower thirds of the face, variations in which have a major influence on the attractiveness of the face. These changes involve facial width, height, and depth. Changes in measurements of length, angles, and proportions found in the sample considered were also analyzed.